Knowledge Translation to Practice and Competency in Translation Methods - Mark Avery (ACHSM, 2023)
Translation or implementation science involves implementing intervention to enhance uptake and use of evidence and knowledge to improve outcomes in health care [1]. Translation sciences play a critical role in health, aged and social care delivery bridging the gap between research and practical patient or client care. This interdisciplinary field encompasses a wide range of activities, from translating health related literature and research findings into clinical and operational practice; to facilitating effective communication between carers and providers; and consumers from diverse linguistic and cultural backgrounds.....